STUDI KANDUNGAN LOGAM Pb DALAM BATANG DAN DAUN KANGKUNG (Ipomoea reptans) YANG DIREBUS DENGAN PENAMBAHAN NaCl DAN ASAM ASETAT - Kohar, Indrajati; Hardjo, Poppy Hartatie; Jonatan, Melyana; Agustanti, Onie (Makara Journal of Science, 2004)
Study on The Content of Pb in Twigs And Leaves of Kangkung (Ipomoea reptans Poir) Boiled With The Addition of NaCl And Acetic Acid. Kangkung is a kind of favorable vegetables that used to grow near a river, and is cultivated and watered with water from the river. If the river is polluted by heavy metals, there is a risk that the plant is contaminated too. A study on the content of Pb in kangkung planted in Pb contaminated media has been conducted, and it was proven that Pb was found in the plant. Land kangkung (Ipomoea reptans) was used as sample, and was planted in hydrophonic media, and watered with Multigrow Complete Plant Food (2000 mg/L) and Pb solution (2 mg/L) twice a day. Samples were taken based on the age of 54 days, then the twigs and leaves were boiled in different ways: I. Boiled with no addition, II. Boiled with addition of NaCl , and III. Boiled with addition of acetic acid. IV. Unboiled sample as the control. Inductively Coupled Plasma Spectrometer (ICPS) Fison 3410+ was used to measure the Pb content. It was shown that boiling the kangkung reduced the Pb content in the leaves as well as in the twigs; however, the acetic acid addition showed the least effect. In the leaves the three different ways of boiling did not show significant different, while in twigs the different was significant.